Creation and delivery of a complex 3D geological survey for the Glasgow area and its application to urban geology. (13th November 2018) - Kearsey, T. I.; Whitbread, K.; Arkley, S. L. B.; Finlayson, A.; Monaghan, A. A.; McLean, W. S.; Terrington, R. L.; Callaghan, E. A.; Millward, D.; Campbell, S. D. G.
ABSTRACT: The Glasgow area has a combination of highly variable superficial deposits and a legacy of heavy industry, quarrying and mining. These factors create complex foundation and hydrological conditions, influencing the movement of contaminants through the subsurface and giving rise locally to unstable ground conditions. Digital geological three-dimensional models developed by the British Geological Survey are helping to resolve the complex geology underlying Glasgow, providing a key tool for planning and environmental management. The models, covering an area of 3200km 2 to a depth of 1.2km, include glacial and post-glacial deposits and the underlying, faulted Carboniferous igneous and sedimentary rocks. Control data, including 95, 000 boreholes, digital mine plans and published geological maps, were used in model development. Digital outputs from the models include maps of depth to key horizons, such as rockhead or depth to mine workings. The models have formed the basis for the development of site-scale high-resolution geological models and provide input data for a wide range of other applications from groundwater modelling to stochastic lithological modelling.